Curable organopolysiloxane composition for transducer, cured product thereof, and transducer provided with cured product

A tailored organopolysiloxane composition with controlled molecular weight and cross-linking density addresses the issue of poor return properties in sensors by achieving low storage modulus and loss tangent, enhancing its suitability as a dielectric layer in transducers.

CN119894984APending Publication Date: 2025-04-25DOW TORAY CO LTD
View PDF 29 Cites 0 Cited by

Patent Information

Application Number
CN202380065861.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-05
Filing Date
2023-09-29
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing exchange materials, particularly in sensors, lack good return properties after deformation due to external stress, with a need for improved performance in terms of low storage modulus and low loss tangent across a wide frequency range.

Method used

A specific formulation of organopolysiloxane composition with controlled molecular weight and cross-linking density, using specific ratios of molecular weight to cross-linking parameter (px1) within certain ranges, along with catalysts and fillers, to achieve low storage modulus and low loss tangent.

Benefits of technology

The composition exhibits excellent electrical and mechanical properties, with improved return characteristics after deformation, making it suitable for use as a dielectric layer in transducers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005309896370000051
    Figure BDA0005309896370000051
  • Figure BDA0005309896370000271
    Figure BDA0005309896370000271
  • Figure BDA0005309896370000281
    Figure BDA0005309896370000281
Patent Text Reader

Abstract

Provided are: a curable organopolysiloxane composition which provides a cured organopolysiloxane having viscoelastic properties (in particular, return properties after deformation due to external stress) that are particularly suitable as a dielectric layer for transducers; and a use for the curable organopolysiloxane composition. A curable organopolysiloxane composition for a transducer, which contains: (a) a chain organopolysiloxane having a weight average molecular weight (Mw (a)) of less than 8.0 * 104 and having a curing reactive group, or a mixture thereof; the organic hydrogen polysiloxane comprises (b1) a cross-linking agent and (b2) a chain extender; and (c) a hydrosilylation reaction catalyst in which the value (= Mw (a) / px1) obtained by dividing the value of px1, defined by px1 = {Hb1 / Hb2} / {(Hb1 + Hb2) / Vi}, by Mw (a) is in the range of 1,000-8,000 with respect to the Si-H substance amount (Hb1, Hb2) in the components (b1) and (b2) and the substance amount (Vi) of the curing reactive group in the component (a).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a curable organopolysiloxane composition for a transducer, characterized in that it provides an organopolysiloxane cured product, which exhibits a low storage modulus in a wide frequency range, has a small loss tangent, and has viscoelastic properties that are particularly suitable for use as a dielectric layer for a transducer. The present invention also relates to a use of the organopolysiloxane cured product as a transducer component, an electronic material, or a display device component. Background Art

[0002] Electroactive silicone materials can achieve high energy density due to their mechanical and / or electrical properties, specifically, high relative dielectric constant, high dielectric breakdown strength, and low Young's modulus, and are excellent in mechanical strength (specifically, tensile strength, tear strength, elongation, etc.) when used as a dielectric layer of a transducer, so they can achieve durability and practical displacement, and can be preferably used as transducer materials. For example, the applicant and others disclosed that a cured organopolysiloxane containing a fluoroalkyl group has a high relative dielectric constant and is useful as a transducer material (Patent Document 1 or Patent Document 2). Furthermore, the applicant and others in this case disclosed a curable organopolysiloxane composition that has excellent coating properties and mechanical strength and is suitable as a transducer material (Patent Document 3).

[0003] In addition, the applicants of this case proposed a parameter related to the crosslinking density in the organopolysiloxane composition (defined as p x1 ) in the range of 0.1 to 6.0, a curable organopolysiloxane composition for a transducer containing a tackifier and the like provides an organopolysiloxane cured product having excellent adhesive strength and conformability (Patent Document 4).

[0004] However, in recent years, in the field of transducer materials represented by actuators, there is a strong demand for electroactive silicone materials to improve good return characteristics after deformation caused by external stress of sensors, etc., but including Patent Document 4, there is no specific disclosure of a curable organopolysiloxane composition for transducers that provides an organopolysiloxane cured product with good return characteristics after deformation (specifically, a low storage modulus in a wide frequency range and a small loss tangent).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Patent Publication No. WO2014 / 105959

[0008] Patent Document 2: International Patent Publication No. WO2015 / 098072

[0009] Patent Document 3: International Patent Publication No. WO2020 / 116440

[0010] Patent Document 4: International Patent Application No. PCT / JP2022 / 026764 (not published at the time of application) Summary of the invention

[0011] Problems to be solved by the invention

[0012] The present invention has been made to solve the above-mentioned problems, and its object is to provide a curable organopolysiloxane composition which exhibits a low storage modulus in a wide frequency range and a small loss tangent, thereby having good return characteristics after deformation such as press-in of a sensor, and to provide an organopolysiloxane cured product having viscoelastic properties that is particularly suitable as a dielectric layer for a transducer.

[0013] Likewise, an object of the present invention is to provide use of the curable organopolysiloxane composition as various transducer materials such as sensors.

[0014] Solutions for solving problems

[0015] The inventors of the present invention have conducted intensive research and found that by selectively using a chain organopolysiloxane or a mixture thereof having a weight average molecular weight Mw(a) of less than 8.0×10 4 and is a parameter related to the crosslinking density in the organopolysiloxane composition. x1 The value obtained by dividing Mw(a) by the value of x1 The present invention has been completed by providing a curable organopolysiloxane composition for a transducer having a SiH / Vi ratio in the range of 1,000 to 8,000, preferably a SiH / Vi ratio of less than 1 (specifically, in the range of 0.1 to 0.99), which can solve the above-mentioned problems.

[0016] Specifically, the above problems are solved by the following curable organopolysiloxane composition for transducer, which comprises:

[0017] (a) The weight average molecular weight of the whole component is less than 8.0×10 4 , a linear or branched organopolysiloxane or a mixture thereof having at least two curing reactive groups containing a carbon-carbon double bond in the molecule;

[0018] (b1) an organohydrogenpolysiloxane having at least one silicon-bonded hydrogen atom in a side chain portion of the molecular chain, having no silicon-bonded hydrogen atom at at least one end of the molecular chain, and having at least two silicon-bonded hydrogen atoms in the molecule;

[0019] (b2) an organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at both ends of the molecular chain and at least two silicon-bonded hydrogen atoms in the molecule; and

[0020] (c) an effective amount of a catalyst for a hydrosilylation reaction,

[0021] About this composition

[0022] The amount of silicon-bonded hydrogen atoms in component (b1) (H b1 ),

[0023] The amount of hydrogen atoms bonded to silicon atoms in component (b2) (H b2 ),as well as

[0024] The amount of curing reactive groups containing carbon-carbon double bonds in component (a) (Vi),

[0025] By the following relationship:

[0026] p x1 ={H b1 / H b2} / {(H b1 +H b2 ) / Vi}

[0027] Defined p x1 The value obtained by dividing Mw(a) by the value of is in the range of 1,000 to 8,000.

[0028] Here, the sum of the amounts of silicon-bonded hydrogen atoms of components (b1) and (b2) is preferably in the range of 0.1 to 0.99 mol relative to 1 mol of carbon-carbon double bonds in component (a), and component (a) is preferably a linear or branched organopolysiloxane or a mixture thereof having curing reactive groups containing carbon-carbon double bonds at both ends of the molecular chain. Furthermore, the above composition may further contain (d) a reinforcing filler and / or (e) a tackifier. In addition, the composition is preferably measured at 25°C using a viscoelasticity measuring device at a shear rate of 0.1 (S -1 ) The overall viscosity of the composition measured is in the range of 100 to 2,000 Pa·s.

[0029] The storage modulus (G') of the organopolysiloxane cured product obtained by curing the present composition at 23°C is preferably 0.1 and 1 Hz at 5.00 × 10 3~1.00×10 5 Pa, and at these measurement frequencies, the loss tangent is less than 0.3. It should be noted that the loss tangent (tanδ) is the value obtained by dividing the loss modulus (G") by the storage modulus (G') at the measurement frequency (=G" / G').

[0030] Furthermore, the above-mentioned problems are preferably solved by a cured organopolysiloxane obtained by curing or semi-curing the above-mentioned composition and its use as a dielectric layer for a transducer, a transducer having a structure in which at least one layer of the cured organopolysiloxane is sandwiched between at least a pair of electrode layers, and a method for manufacturing the same.

[0031] Effects of the Invention

[0032] According to the present invention, a curable organopolysiloxane composition is provided, which has excellent electrical properties, exhibits a low storage modulus in a wide frequency range, and has a small loss tangent, so it has good return characteristics after deformation, and provides an organopolysiloxane cured product having viscoelastic properties that is particularly suitable as a dielectric layer for a transducer. Further, according to the present invention, a transducer is provided, which contains an electroactive organosilicon material that can be used as a film-shaped or sheet-shaped transducer member, especially as a dielectric layer for a transducer, and has good return characteristics after deformation, and a method for manufacturing the same. DETAILED DESCRIPTION

[0033] First, the curable organopolysiloxane composition for transducers of the present invention is described in detail. Hereinafter, in this specification, "transducer" refers to all electronic devices having the function of converting mechanical energy and electrical energy into each other, and is a concept including sensors, speakers, actuators, and generators. The curable organopolysiloxane composition of the present invention has the characteristics before and after curing that are preferred in terms of its cured product, especially the cured product film, being used as a component constituting the above-mentioned transducer.

[0034] In this specification, "weight average molecular weight" refers to the weight average molecular weight measured by gel permeation chromatography (GPC) and converted to standard polystyrene. It should be noted that the meaning and calculation method of the weight average molecular weight when component (a) is a mixture are described below.

[0035] The composition of the present invention comprises at least the following:

[0036] (a) The weight average molecular weight of the whole component is less than 8.0×10 4 , a linear or branched organopolysiloxane or a mixture thereof having at least two curing reactive groups containing a carbon-carbon double bond in the molecule;

[0037] (b1) an organohydrogenpolysiloxane having at least one silicon-bonded hydrogen atom in a side chain portion of the molecular chain, having no silicon-bonded hydrogen atom at at least one end of the molecular chain, and having at least two silicon-bonded hydrogen atoms in the molecule;

[0038] (b2) an organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at both ends of the molecular chain and at least two silicon-bonded hydrogen atoms in the molecule; and

[0039] (c) an effective amount of a catalyst for a hydrosilylation reaction,

[0040] Further,

[0041] Preferably, it contains (d) a reinforcing filler and / or (e) a tackifier,

[0042] A hydrosilylation reaction inhibitor, other organic solvents, and other optional additives may optionally be included.

[0043] The composition of the present invention is a composition that is cured by hydrosilylation reaction between alkenyl groups and silicon-bonded hydrogen atoms, and has the advantages of being relatively fast in curing and easy to control the reaction. The curing reaction can be carried out by heating, irradiation with high-energy rays, or a combination of these.

[0044] [Weight Average Molecular Weight (Mw(a)) of Component (a) and Component (a) in Composition]

[0045] Component (a) is an essential component for achieving the technical effects of the present invention, especially the good return characteristics after deformation, and its weight average molecular weight (Mw(a)) is less than 8.0×10 4 , is a linear or branched organopolysiloxane or a mixture thereof having at least two curing reactive groups containing a carbon-carbon double bond in the molecule.

[0046] Component (a) is the above-mentioned linear organopolysiloxane or a mixture thereof. The weight average molecular weight of component (a) in the composition can be calculated as follows.

[0047]

[0048] Mwk and wfk are the weight average molecular weight of the organopolysiloxane constituting the kth component (a) and the weight fraction in all components (a).

[0049] The weight average molecular weight (Mw(a)) of component (a) must be less than 8.0×10 4 If the weight average molecular weight of component (a) in the composition exceeds the upper limit, even if the parameter p related to the crosslinking density described later is x1The value obtained by dividing Mw(a) by the value of Mw(a) is in the range of 1,000 to 8,000. In the cured organopolysiloxane thereof, the good return characteristics after deformation and the viscoelastic properties thereof, which are the purposes of the present invention, may not be achieved. It should be noted that, as described above, component (a) may be a mixture of the above-mentioned chain organopolysiloxanes. As a whole, component (a) may have a weight average molecular weight less than the above lower limit. However, it is more preferred that, in each of the above-mentioned chain organopolysiloxanes constituting component (a), the weight average molecular weight thereof is less than 8.0×10 4 It is particularly preferred that the composition does not contain a weight average molecular weight of 8.0×10 4 The above-mentioned chain organopolysiloxane.

[0050] The organopolysiloxane as component (a) has a chain structure, specifically, a straight-chain or branched organopolysiloxane, preferably a straight-chain or branched organopolysiloxane having a curing reactive group containing a carbon-carbon double bond at both ends of the molecular chain, and particularly preferably a straight-chain organopolysiloxane having a curing reactive group containing a carbon-carbon double bond at both ends of the molecular chain.

[0051] Examples of the curing reactive group containing a carbon-carbon double bond in the organopolysiloxane of component (a) include: a curing reactive group selected from alkenyl groups having 2 to 20 carbon atoms such as vinyl groups; and groups containing a (meth)acryloyl group such as 3-acryloxypropyl groups and 3-methacryloxypropyl groups.

[0052] The organopolysiloxane as component (a) may also contain a group selected from a monovalent hydrocarbon group, a hydroxyl group, and an alkoxy group having 1 to 3 carbon atoms and having no carbon-carbon double bond in the molecule. In addition, with respect to the monovalent hydrocarbon group, a portion of its hydrogen atoms may be substituted by a halogen atom or a hydroxyl group, and when used as a dielectric layer, a dielectric functional group described below may be introduced. Industrially preferred are methyl, phenyl, hydroxyl, alkoxy, and dielectric functional groups described below. It should be noted that when component (a) contains a hydroxyl group, etc., the component has condensation reactivity in addition to hydrosilylation reaction curing properties.

[0053] Here, when using component (a), it is necessary to select or design the amount (Vi) of the curing reactive group containing a carbon-carbon double bond such as an alkenyl group in component (A) so that the parameter p related to the crosslinking density and crosslinking structure of the present composition described later is x1 The value obtained by dividing Mw(a) by the value of is in the range of 1,000 to 8,000.

[0054] Preferably, the component (a) in the present invention can be introduced into the molecule by (C p F 2p+1A fluoroalkyl group represented by )-R- (R is an alkylene group having 1 to 10 carbon atoms, and p is an integer of 1 to 8) is preferred as a dielectric functional group. From the viewpoint of dielectric properties, economic efficiency, ease of manufacture, and molding processability of the resulting curable organopolysiloxane composition, a preferred group is a group in which p=1, i.e., a trifluoropropyl group.

[0055] Preferably, component (a) may be at least partially or entirely composed of one or more of (a1f) having at least two alkenyl groups having 2 to 12 carbon atoms in the molecule, and 10 mol% or more of all substituents on silicon atoms are composed of (C p F 2p+1 An organopolysiloxane containing a fluoroalkyl group as a fluoroalkyl group represented by )-R- (R is an alkylene group having 1 to 10 carbon atoms, and p is an integer of 1 to 8). By using such a component (a1f) as a main agent, a fluoroorganopolysiloxane cured film having excellent dielectric properties can be obtained.

[0056] [Component (b): (b1) and (b2)]

[0057] Component (b) is an organohydrogenpolysiloxane having at least two silicon-bonded hydrogen atoms in the molecule, and functions as the (b1) crosslinking agent or (b2) chain extender of component (a).

[0058] Specifically, component (b1) is an organohydrogenpolysiloxane having at least one silicon-bonded hydrogen atom in the side chain of the molecular chain, having no silicon-bonded hydrogen atom at at least one end of the molecular chain, and having at least two silicon-bonded hydrogen atoms in the molecule, and is distinguished from component (b2) in that it has no silicon-bonded hydrogen atoms at both ends, and preferably has a structure in which both ends of the molecular chain are capped with functional groups that are non-reactive to hydrosilylation reaction (particularly reaction with the above-mentioned component (A)). Such component (b1) has hydrogen atoms bonded to silicon atoms constituting the main chain of the siloxane molecule (= hydrogen atoms bonded to the side chain portion), so that an intermolecular crosslinking structure is formed between the hydrogen atoms on the side chain and the curing reactive groups in component (a), and on the other hand, the chain extension effect of the crosslinked product is limited.

[0059] Component (b2) is an organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at both ends of the molecular chain and at least two silicon-bonded hydrogen atoms in the molecule, preferably having two (= only at both ends of the molecular chain) silicon-bonded hydrogen atoms. Such component (b2) is a chain extender that reacts with the curing reactive group in component (a) to introduce a long siloxane molecular structure into the crosslinked product, and can impart moderate softness and elasticity to the crosslinked product.

[0060] Examples of such component (b1) include 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, tris(dimethylhydrogensiloxy)methylsilane, tris(dimethylhydrogensiloxy)phenylsilane, methylhydrogenpolysiloxane having both molecular chain terminals blocked with trimethylsiloxy groups, dimethylsiloxane / methylhydrogensiloxane copolymer having both molecular chain terminals blocked with dimethylhydrogensiloxy groups, methylhydrogensiloxane / diphenylsiloxane copolymer having both molecular chain terminals blocked with trimethylsiloxy groups, methylhydrogensiloxane / diphenylsiloxane / dimethylsiloxane copolymer having both molecular chain terminals blocked with trimethylsiloxy groups, methylhydrogensiloxane / dimethylsiloxane / trifluoropropylmethylsiloxane copolymer having both molecular chain terminals blocked with trimethylsiloxy groups, hydrolyzed condensates of trimethoxysilane, and (CH 3 ) 2 HSiO 1 / 2 Unit and SiO 4 / 2 The copolymer composed of (CH 3 ) 2 HSiO 1 / 2 Unit, SiO 4 / 2 Unit and (C 6 H 5 )SiO 3 / 2 Unit composition, and mixtures of two or more thereof.

[0061] Examples of such component (b2) include dimethylsiloxane having both ends of the molecular chain capped with dimethylhydrogensiloxy groups, dimethylsiloxane / diphenylsiloxane copolymers having both ends of the molecular chain capped with dimethylhydrogensiloxy groups, dimethylsiloxane / trifluoropropylmethylsiloxane copolymers having both ends of the molecular chain capped with dimethylhydrogensiloxy groups, dimethylsiloxane / methylhydrogensiloxane copolymers having both ends of the molecular chain capped with dimethylhydrogensiloxy groups, and mixtures of two or more thereof.

[0062] [Parameter p xl ]

[0063] The curable organopolysiloxane composition for transducers according to the present invention is characterized in that, in relation to component (a), component (b1), and component (b2), p defined by the following parameters: xl The value obtained by dividing Mw(a) by the value of is within the specified range. xl is a parameter for expressing the crosslinking density and the crosslinking structure between molecules of the cured product obtained by curing the present composition.

[0064] The number of hydrogen atoms bonded to the silicon atoms in the component (b1) (H b1 ),

[0065] The number of hydrogen atoms bonded to silicon atoms in component (b2) (H b2 ),as well as

[0066] The total number of curing reactive groups containing carbon-carbon double bonds in component (a) (Vi)

[0067] By the following relationship:

[0068] p x1 ={H b1 / H b2} / {(H b1 +H b2 ) / Vi}

[0069] Definition, the types and amounts of ingredients (a), (b1) and (b2) need to be determined by p x1 The value obtained by dividing Mw(a) by the value of is in the range of 1,000 to 8,000. xl When the value of is outside the above range, in the organopolysiloxane cured product, good return characteristics after deformation and viscoelastic properties may not be achieved. It should be noted that, as described above, when the weight average molecular weight of component (a) exceeds the above upper limit, even if, for example, Mw(a) is divided by p x1 The value obtained by changing the value of p to be within the above range may sometimes fail to achieve the technical effect of the present invention. It should be noted that in the present invention, p x1 The value of is preferably in the range of 6.5 to 20.0.

[0070] By p x1 The value obtained by dividing Mw(a) by the value of x1 In the present composition, the weight average molecular weight (Mw(a)) of component (a) is less than 8.0×10 4 , and comprising two organohydrogenpolysiloxanes, component (b1) having a function as a crosslinking agent, and component (b2) having a function as a chain extender. {H b1 / H b2} represents the ratio of Si-H in the crosslinking agent and the chain extender. If these ratios are within a specific range, a crosslinking structure is formed with a moderately long intermolecular distance for the curing reactive groups in component (a), thereby easily achieving a moderate hardness and a rubber-like storage modulus. Furthermore, if the ratio (H) of the composition as a whole is divided by the ratio (H) representing the "SiH / Vi ratio", b1 +H b2 ) / Vi value and return p x1The value of Mw(a) (a parameter describing the cross-linked structure) divided by the weight average molecular weight of component (a) is in the range of 1,000 to 8,000. Based on the use of component (a) having the above-mentioned weight average molecular weight, the organic polysiloxane cured product as a cross-linked product exhibits a low storage modulus in a wide frequency region and tends to have a smaller loss tangent. As a result, a film or sheet-like member composed of the cured product can achieve good return characteristics after deformation caused by the indentation of a dielectric layer for a transducer such as a sensor.

[0071] The amount of component (b1) and component (b2) used needs to satisfy the above range. Preferably, the sum of the silicon-bonded hydrogen atoms of component (b1) and component (b2) (hereinafter referred to as "SiH / Vi ratio") is in the range of 0.1 to 10 mol per 1 mol of carbon-carbon double bonds in component (a), more preferably less than 1.0 mol, specifically, in the range of 0.1 to 0.99 mol. From the viewpoint of achieving the curability and good viscoelasticity of the curable organopolysiloxane composition involved in the present invention, the SiH / Vi ratio is particularly preferably in the range of 0.30 to 0.90, 0.40 to 0.80, or 0.50 to 0.75 mol.

[0072] [Component (c)]

[0073] Component (c) is a catalyst for promoting the hydrosilylation reaction of component (a) and component (b), and examples thereof include: platinum-based catalysts, rhodium-based catalysts, palladium-based catalysts, nickel-based catalysts, iridium-based catalysts, ruthenium-based catalysts, and iron-based catalysts, preferably platinum-based catalysts. As the platinum-based catalyst, examples thereof include platinum fine powder, chloroplatinic acid, alcohol solution of chloroplatinic acid, platinum-alkenylsiloxane complex, platinum-olefin complex, platinum-carbonyl complex, and catalysts in which these platinum-based catalysts are dispersed or encapsulated by thermoplastic resins such as silicone resins, polycarbonate resins, and acrylic resins, and platinum-alkenylsiloxane complexes are particularly preferred. 1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex of platinum is particularly preferred, and it is preferably added in the form of an alkenylsiloxane solution of the complex. In addition, from the viewpoint of improving the operability and the pot life of the composition, a microparticle-containing hydrosilylation catalyst containing platinum dispersed or encapsulated by a thermoplastic resin can also be used. It should be noted that, as a catalyst for accelerating the hydrosilylation reaction, a non-platinum metal catalyst such as iron, ruthenium, or iron / cobalt can be used.

[0074] In addition, the hydrosilylation reaction catalyst as component (c) may be a hydrosilylation reaction catalyst that does not show activity without irradiation with high-energy rays, but shows activity in the composition by irradiation with high-energy rays, so-called high-energy ray-activated catalyst or photoactivated catalyst. By using such a component (c), the composition as a whole can achieve the following characteristics: it can be cured even at low temperatures by irradiation with high-energy rays as a trigger, has excellent storage stability, and is easy to control the reaction, so it is excellent in workability.

[0075] Examples of high-energy rays include ultraviolet rays, gamma rays, X-rays, alpha rays, electron beams, and the like. In particular, ultraviolet rays, X-rays, and electron beams irradiated by commercially available electron beam irradiation devices are included. Ultraviolet rays are preferred from the perspective of catalyst activation efficiency, and ultraviolet rays with a wavelength of 280 to 380 nm are preferred from the perspective of industrial utilization. In addition, the irradiation amount varies depending on the type of high-energy ray-activated catalyst. In the case of ultraviolet rays, the cumulative irradiation amount at a wavelength of 365 nm is preferably 100 mJ / cm 2 ~100J / cm 2 within the range.

[0076] Specific examples of component (c) include (methylcyclopentadienyl)trimethylplatinum (IV), (cyclopentadienyl)trimethylplatinum (IV), (1,2,3,4,5-pentamethylcyclopentadienyl)trimethylplatinum (IV), (cyclopentadienyl)dimethylethylplatinum (IV), (cyclopentadienyl)dimethylacetylplatinum (IV), (trimethylsilylcyclopentadienyl)trimethylplatinum (IV), (methoxycarbonylcyclopentadienyl)trimethylplatinum (IV), (dimethylphenylsilylcyclopentadienyl)trimethylcyclopentadienylplatinum (IV), trimethyl(acetylacetylacetonate)platinum (IV), trimethyl(3,5 -heptanedione) platinum (IV), trimethyl (methyl acetoacetate) platinum (IV), bis (2,4-pentanedione) platinum (II), bis (2,4-hexanedione) platinum (II), bis (2,4-heptanedione) platinum (II), bis (3,5-heptanedione) platinum (II), bis (1-phenyl-1,3-butanedione) platinum (II), bis (1,3-diphenyl-1,3-propanedione) platinum (II), bis (hexafluoroacetylacetonate) platinum (II), among which (methylcyclopentadienyl) trimethyl platinum (IV) and bis (2,4-pentanedione) platinum (II) are preferred from the aspects of versatility and ease of acquisition.

[0077] The amount of component (c) used is an effective amount and is not particularly limited, but as long as it is an amount that promotes the curing of the curable organopolysiloxane composition of the present invention, it is not particularly limited. Specifically, the metal atoms in the catalyst are 0.01 to 1,000 ppm in mass units relative to the sum of components (a) to (c) (the whole is set to 100% by mass), and the platinum metal atoms in component (c) are preferably in an amount within the range of 0.1 to 500 ppm. This is because if the content of component (c) is less than the lower limit of the above range, the curing may sometimes become insufficient, and if it exceeds the upper limit of the above range, in addition to being uneconomical, it may sometimes have an adverse effect on the coloring and transparency of the obtained cured product.

[0078] [Ingredient (d)]

[0079] In the curable organopolysiloxane composition of the present invention, xl On the basis of setting the value of to the previous range, for the organopolysiloxane cured product obtained using the present composition, in particular for the purpose of further improving the mechanical strength such as hardness, a reinforcing filler (d) may be further added. In the case where the present composition is cured to obtain a cured film for a transducer as a dielectric layer, the reinforcing filler as component (d) is preferably at least partly inorganic oxide microparticles represented by silicon dioxide, and preferably contains a reinforcing filler as component (d) or a composite thereof that is surface-treated with one or more organosilicon compounds and has different average BET specific surface areas within a certain range relative to the sum of the components (i.e., components (a) to (e)) in the composition that form non-volatile solid components through a curing reaction.

[0080] Here, from the viewpoint of mechanical strength of the cured product, the reinforcing particles are preferably one or more reinforcing inorganic particles having an average primary particle size of less than 50 nm, and examples thereof include: fumed silica, wet silica, crushed silica, calcium carbonate, diatomaceous earth, finely crushed quartz, various metal oxide powders other than alumina / zinc oxide, glass fiber, carbon fiber, etc., and these are treated with one or more organosilicon compounds described later. The shape thereof is not particularly limited, and any shape of reinforcing particles such as particles, plates, needles, and fibers can be used.

[0081] As a preferred example, from the viewpoint of improving the mechanical strength of the dielectric layer, an average primary particle size of 10 nm or less, partially agglomerated, and having a hydrophilic or hydrophobic fumed silica or a metal oxide complex thereof with different BET specific surface areas as described later can be cited. Furthermore, from the viewpoint of improving dispersibility, it is preferred that the fumed silica or a metal oxide complex thereof be treated with disilazane or a silane coupling agent described later. Two or more of these reinforcing inorganic particles may also be used in combination.

[0082] In the present invention, the reinforcing filler used in the dielectric layer comprises:

[0083] (d1) Surface-treated with one or more organosilicon compounds, with an average BET specific surface area exceeding 100 m 2 / g of reinforcing particles or their complexes; and

[0084] (d2) Surface-treated with one or more organic silicon compounds, with an average BET specific surface area of ​​10 to 100 m 2 / g range of reinforcing particles or their complexes, and

[0085] The mass ratio of component (d1) to component (d2) is in the range of 50:50 to 99:1, and can be in the range of 70:30 to 97:3, and preferably in the range of 70:30 to 95:5. If the mass ratio deviates from the above range, the viscosity of the curable organopolysiloxane composition before curing may increase, or the mechanical strength and dielectric breakdown strength after curing may decrease.

[0086] By blending the reinforcing fillers as the above-mentioned components (d1) and (d2) into the composition, the mechanical strength and dielectric breakdown strength of the organopolysiloxane cured product obtained by curing the curable organopolysiloxane composition of the present invention can be increased.

[0087] [Content of ingredient (d) (w f )]

[0088] In the composition of the present invention, when the sum of the components that form the non-volatile solid content by curing reaction, that is, the total of components (a) to (e) is taken as 100% by mass, the content (w f ) is preferably in the range of 5 to 40% by mass, and particularly preferably in the range of 5 to 30% by mass. The dielectric film used in the transducer requires deformability and moderate resilience. However, if the content of component (d) (w f ) exceeds the above upper limit, the viscosity of the composition tends to increase, becoming high viscosity, and sometimes it is difficult to achieve uniform and thin film coating. Further, the storage modulus after curing tends to increase, becoming too hard, and therefore sometimes the performance in the transducer application cannot be fully achieved. On the other hand, if it is lower than the lower limit of the above mass % range, there is a possibility that the physical properties of the curable organopolysiloxane composition after curing become insufficient.

[0089] More preferably, when the total of components (a) to (e) is set to 100% by mass, the sum of components (d1) and (d2) is within the range of 5 to 40% by mass, and can be within the range of 5.0 to 35% by mass, and is particularly preferably within the range of 6.5 to 30% by mass. If the upper limit of the above-mentioned mass % range is exceeded, it is sometimes difficult to achieve uniform and thin film coating, and the storage modulus after curing becomes high. If it is lower than the lower limit of the above-mentioned mass % range, there is a possibility that the physical properties of the curable organopolysiloxane composition after curing become insufficient.

[0090] The reinforcing fillers as the above-mentioned components (d1) and (d2) are preferably surface-treated with one or more organosilicon compounds. The surface treatment with the organosilicon compound is a hydrophobic treatment, but the reinforcing filler surface-treated with the organosilicon compound involved can be uniformly dispersed in the fluoroorganopolysiloxane composition at a high filling rate. In addition, the increase in the viscosity of the composition is suppressed, and the molding processability is improved.

[0091] Examples of the organosilicon compound include low molecular weight organosilicon compounds such as silane, silazane, siloxane or the like; and organosilicon polymers or oligomers such as polysiloxane, polycarbosiloxane or the like. Preferably, the organosilicon compound used for surface treatment most preferably contains at least one selected from hexamethyldisilazane and 1,3-bis(3,3,3-trifluoropropyl)-1,1,3,3-tetramethyldisilazane.

[0092] In the above-mentioned surface treatment, the ratio of the surface treatment agent to the total amount of the filler is preferably in the range of 0.1 mass % to 50 mass %, more preferably in the range of 0.3 mass % to 40 mass %. It should be noted that the treatment amount is the charge ratio of the filler to the surface treatment agent, and the remaining treatment agent is preferably removed after the treatment. In addition, when the treatment is performed as needed, there is no problem in using additives that promote or assist the reaction.

[0093] In the above-mentioned surface treatment, whether the components of the surface treatment agent are chemically or physically fixed to the filler surface is an important parameter. For example, the fixed amount of the surface treatment agent can be analyzed by reacting excess tetraethoxysilane with a composition containing a filler under alkaline conditions and detecting the reaction product by gas chromatography. The amount of the surface treatment agent fixed to the surface of the above-mentioned filler can be 1.0 parts by mass or more, preferably 3.0 parts by mass or more, relative to 100 parts by mass of the filler. Among them, in the case where hexamethyldisilazane and 1,3-bis(3,3,3-trifluoropropyl)-1,1,3,3-tetramethyldisilazane are used as the organosilicon compounds for the surface treatment of the components (d1) and (d2) related to the present invention, the fixing ratio of each on the filler surface can be changed as needed. For example, in the present invention, as described above, a high dielectric functional group can be introduced into a part or all of the components (a) or (b1) and (b2) as a result of (C p F 2p+1 A fluoroalkyl group represented by )-R-(R is an alkylene group having 1 to 10 carbon atoms, and p is an integer of 1 to 8). From the viewpoint of dielectric properties, economy, ease of manufacture, and molding processability of the resulting curable organopolysiloxane composition, a group in which p=1, i.e., a trifluoropropyl group, can be used. In this case, the weight ratio of the treatment components from hexamethyldisilazane and 1,3-bis(3,3,3-trifluoropropyl)-1,1,3,3-tetramethyldisilazane fixed to the surface of the filler can be from 0 to 10. If it deviates from this range, the affinity of component (a) or component (b) to the surface of the filler deteriorates, and there is a possibility that the processability or physical properties after curing will be reduced.

[0094] [Other functional fillers]

[0095] In the curable fluoroorganopolysiloxane composition involved in the present invention, other fillers may be used or not used as desired, for example, high dielectric fillers, thermally conductive inorganic particles, insulating fillers, etc. These inorganic particles sometimes have two or more functions such as the function of serving as reinforcing fillers.

[0096] As an example of a preferred dielectric inorganic particle, one or more inorganic particles selected from the group consisting of a composite metal oxide in which a portion of the barium and titanium parts of titanium oxide, barium titanate, lead zirconate titanate, and barium titanate are replaced with alkaline earth metals, zirconium or rare earth metals such as calcium, strontium, yttrium, neodymium, samarium, and dysprosium can be cited, more preferably titanium oxide, barium titanate, barium zirconate titanate calcium, and strontium titanate, and more preferably titanium oxide and barium titanate. In particular, the dielectric inorganic particles are particularly preferably dielectric inorganic particles having a relative dielectric constant of more than 10 at room temperature and 1kHz. It should be noted that the upper limit of the preferred size (average primary particle size) of the inorganic particles is 20,000nm (20μm), but if the processability of the transducer film described later is considered, it is more preferably 10,000nm (10μm). By using the dielectric inorganic fine particles, the mechanical properties and / or electrical properties of the obtained organopolysiloxane cured product may be further improved, in particular, the relative dielectric constant thereof.

[0097] The insulating inorganic fine particles that can be used in the present invention can be any generally known insulating inorganic material, that is, any material having a volume resistivity of 10 10 ~10 18 The particles of inorganic materials with a resistance of Ω·cm are just not limited, and any shape in particle, sheet, fiber (including whisker) can be used. Specifically, spherical particles, plate-like particles or fibers of ceramics can be listed, and particles of metal silicates such as aluminum oxide, iron oxide, copper oxide, mica or talc, quartz, amorphous silicon dioxide, glass, etc. can be listed as preferred examples of use. In addition, these can also be treated with various surface treatment agents described later. These can be used alone or in combination of two or more. By mixing insulating inorganic particles in the composition, the mechanical strength and dielectric breakdown strength of the fluorine organopolysiloxane cured product can be increased, and the increase of relative dielectric constant can also be observed sometimes.

[0098] As thermally conductive inorganic particles that can be used in the present invention, metal oxide particles such as magnesium oxide, zinc oxide, nickel oxide, vanadium oxide, copper oxide, iron oxide, and silver oxide can be listed; and inorganic compound particles such as aluminum nitride, boron nitride, silicon carbide, silicon nitride, boron carbide, titanium carbide, diamond, and diamond-like carbon can be listed, and zinc oxide, boron nitride, silicon carbide, and silicon nitride are preferred. By mixing one or more of these thermally conductive inorganic particles into the composition, the thermal conductivity of the organopolysiloxane cured product can be increased.

[0099] The mensuration of the average particle size of these inorganic particles can be carried out by the measuring method common in this field.For example, in the case where the average particle size is more than 50nm and less than about 500nm, particle diameter is measured by microscopic observations such as transmission electron microscope (TEM), field emission transmission electron microscope (FE-TEM), scanning electron microscope (SEM), field emission scanning electron microscope (FE-SEM), by obtaining mean value, average primary particle diameter can be measured.On the other hand, in the case where the average particle size is more than about 500nm, the value of average primary particle diameter can be directly obtained by laser diffraction / scattering type particle size distribution measuring device etc.

[0100] The curable organopolysiloxane composition of the present invention may optionally contain (e) a tackifier. In particular, the composition of the present invention is a composition that provides a cured product having a specific crosslinking density and a crosslinking structure between molecules after curing, but by including a tackifier, a chemical bond is formed with the surface of the substrate layer or electrode layer coated with the composition, and strong adhesion and followability may be achieved. In particular, it is effective when the composition is designed so that the electrode layer and the dielectric layer have a chemically bonded structure.

[0101] (e) The amount of thickener used can be appropriately designed according to the desired adhesive force, the type of substrate layer or electrode layer, etc., but from the viewpoint of improving the adhesive strength and followability relative to the substrate layer or electrode layer composed of a thermoplastic resin such as polyethylene terephthalate (PET), it is preferred that the content of component (e) is in the range of 0.1 mass % to 10 mass %, preferably 0.25 mass % to 5.0 mass %, and particularly preferably 0.5 mass % to 2.0 mass %, when the total of components (a) to (e) constituting the composition is set to 100 mass %.

[0102] As a tackifier, an organosilicon compound having at least one alkoxy group bonded to a silicon atom in one molecule is preferred. Examples of the alkoxy group include: methoxy, ethoxy, propoxy, butoxy, and methoxyethoxy, with methoxy being particularly preferred. In addition, as groups bonded to silicon atoms other than the alkoxy groups in the organosilicon compound, examples include: halogen-substituted or non-substituted monovalent hydrocarbon groups such as alkyl, alkenyl, aryl, aralkyl, and halogenated alkyl groups; glycidoxyalkyl groups such as 3-glycidoxypropyl and 4-glycidoxybutyl; epoxycyclohexylalkyl groups such as 2-(3,4-epoxycyclohexyl)ethyl and 3-(3,4-epoxycyclohexyl)propyl; epoxyalkyl groups such as 3,4-epoxybutyl and 7,8-epoxyoctyl; monovalent organic groups containing an acryl group such as 3-methacryloxypropyl; and hydrogen atoms. The organosilicon compound preferably has a group that can react with an alkenyl group or a silicon-bonded hydrogen atom in the present composition, and specifically preferably has a silicon-bonded hydrogen atom or an alkenyl group. In addition, from the aspect of being able to impart good adhesion to various substrates, the organosilicon compound preferably has at least one monovalent organic group containing an epoxy group in one molecule.

[0103] Examples of such organosilicon compounds include organosilane compounds, organosiloxane oligomers, and alkyl silicates. Examples of the molecular structure of the organosiloxane oligomers or alkyl silicates include linear, partially branched linear, branched, cyclic, and network structures, with linear, branched, and network structures being particularly preferred. Examples of the organosilicon compound include silane compounds such as 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 3-methacryloxypropyltrimethoxysilane; siloxane compounds each having at least one silicon-bonded alkenyl group or silicon-bonded hydrogen atom and silicon-bonded alkoxy group in one molecule; a silane compound having at least one silicon-bonded alkoxy group or a mixture of a siloxane compound and a siloxane compound each having at least one silicon-bonded hydroxyl group and silicon-bonded alkenyl group in one molecule; a reaction mixture of an amino group-containing organoalkoxysilane and an epoxy group-containing organoalkoxysilane; an organic compound having at least two alkoxysilyl groups in one molecule and containing a bond other than a silicon-oxygen bond between the silyl groups;

[0104] General formula: R a n Si(OR b ) 4-n

[0105] (Where R a is a monovalent organic group containing an epoxy group, R b is an alkyl group having 1 to 6 carbon atoms or a hydrogen atom. n is a number in the range of 1 to 3)

[0106] The epoxy-containing silane or its partial hydrolysis condensate shown, the reaction mixture of the vinyl-containing siloxane oligomer (including the siloxane oligomer of chain or cyclic structure) and the epoxy-containing trialkoxysilane, methyl polysilicate, ethyl polysilicate and ethyl polysilicate containing epoxy group. The tackifier is preferably a low-viscosity liquid, and its viscosity is not limited, but preferably in the range of 1 to 500 mPa·s at 25°C. In addition, the content of the tackifier is not limited, and is preferably in the range of 0.01 to 10 parts by mass relative to a total of 100 parts by mass of the present composition.

[0107] In the present invention, as a particularly preferred tackifier, a reaction mixture of a vinyl group-containing siloxane oligomer (including a chain or cyclic structure) and an epoxy group-containing trialkoxysilane can be exemplified.

[0108] [Hydrosilylation Reaction Inhibitors]

[0109] The hydrosilylation reaction inhibitor is formulated to inhibit the crosslinking reaction or chain extension reaction between component (a) and component (b), thereby extending the usable time at room temperature and improving the storage stability. Therefore, it is a component that must be formulated in the curable composition of the present invention in practical use.

[0110] Examples of the hydrosilylation reaction inhibitor include acetylene compounds, enyne compounds, organic nitrogen compounds, organic phosphorus compounds, and oxime compounds. Specifically, examples include acetylene alcohols such as 3-methyl-1-butyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 3-methyl-1-pentyn-3-ol, 1-ethyn-1-cyclohexanol, and phenylbutanol; enyne compounds such as 3-methyl-3-pentene-1-yne and 3,5-dimethyl-1-hexyn-3-yne; methylenylcyclosiloxanes such as 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane and 1,3,5,7-tetramethyl-1,3,5,7-tetrahexenylcyclotetrasiloxane; and benzotriazole.

[0111] The amount of the hydrosilylation reaction inhibitor is an amount effective for extending the usable time of the film-forming curable fluorinated organopolysiloxane composition of the present invention at room temperature and improving the storage stability. Usually, the amount of the hydrosilylation reaction inhibitor is in the range of 0.001 to 5% by mass, preferably in the range of 0.01 to 2% by mass, per 100% by mass of component (a), but it is preferably appropriately selected according to the type of this component, the performance and content of the platinum catalyst, the amount of curing reactive groups (alkenyl, etc.) in component (a), the amount of silicon-bonded hydrogen atoms in component (b), etc.

[0112] [Use of solvent]

[0113] The curable organopolysiloxane composition of the present invention can be used directly for curing reaction, but on the other hand, in the case where the composition or part of its components is solid or viscous liquid, in order to improve its miscibility and operability, an organic solvent can be used as needed. In particular, when the curable organopolysiloxane composition of the present invention is applied in a film form, the viscosity can be adjusted by using a solvent in the range of 100 to 50,000 mPa·s for the overall viscosity, and when diluted with a solvent, it can be used in the range of 0 to 2000 parts by mass relative to the sum of the above components (a) to (c) (100 parts by mass). That is, in the composition of the present invention, the solvent can be 0 parts by mass, and it is preferably a solvent-free type. In particular, by selecting a polymer with a low degree of polymerization in the curable organopolysiloxane composition of the present invention, there are the following advantages: it can be designed to be solvent-free, and no fluorine-based solvents, organic solvents, etc. remain in the film obtained by curing, which can eliminate the problem of environmental load and the influence of solvents on electronic devices. In addition, the amount of the solvent used can be 10 parts by mass or less, preferably 5 parts by mass or less, relative to the sum of the above-mentioned components (a) to (c) (100 parts by mass), and preferably a low-solvent type composition. In addition, in particular, the composition for the electrode layer can be diluted with a solvent as described in the embodiments below, and applied as a film by spraying.

[0114] Preferably, the organic solvent is one or more organic solvents selected from the following solvents or a mixed solvent thereof:

[0115] (f1) organic polar solvent;

[0116] (f2) low molecular weight siloxane solvent; and

[0117] (f3) halogen solvents,

[0118] It is preferred to use an organic solvent having a boiling point of 80°C or more and less than 200°C. It should be noted that it may also be a mixed solvent of different types or the same type of organic solvents in different ratios. Preferably, the organic solvent comprises at least one low molecular weight siloxane-based solvent selected from hexamethyldisiloxane and octamethyltrisiloxane and a mixed solvent thereof, which are commercially available under the names of OS-10, O-20 and OS-2 from DOW SILICONES CORPORATION. In addition, in the case where the fluoroalkyl content in the curable elastomer composition is high, the arbitrary use of these low molecular weight siloxane-based solvents and the above-mentioned halogen-based solvents is also included in the preferred embodiment of the present invention.

[0119] [Viscosity and thixotropy of composition]

[0120] The composition of the present invention can be applied to a substrate layer or an electrode layer and cured into a film for use. In particular, when its overall viscosity and thixotropy are within a certain range, it is easy to be evenly applied to the substrate layer, etc., and sometimes the adhesion and followability with the substrate / electrode layer during curing can be improved. In particular, a composition having a thixotropic index defined below and containing a tackifier is particularly preferred in terms of easy formation of adhesion and chemical bonds at the interface.

[0121] [Overall viscosity]

[0122] The curable organopolysiloxane composition used in the present invention was subjected to a shear test at 25° C. using a viscoelasticity measuring apparatus at a shear rate (hereinafter, sometimes referred to as “shear rate”) of 0.1 (S -1 ) is preferably in the range of 5 to 5,000 Pa·s, particularly preferably in the range of 100 to 2,000 Pa·s. For the purpose of setting the preferred viscosity range, the amount of the organic solvent used may be adjusted, but a low-solvent type or a solvent-free type (= solvent-free type) may also be used.

[0123] [Thixotropic Index (TI)]

[0124] The curable organopolysiloxane composition of the present invention preferably has excellent fluidity and moderate thixotropic behavior. Thus, it is possible to achieve properties of low overall viscosity and excellent uniform coating properties. Specifically, for the composition, at a shear rate of 0.1 (S -1 ) measured the viscosity of the entire composition (η 0.1 ) and at a shear rate of 10.0(S -1 ) measured the viscosity of the entire composition (η 10.0 ) ratio, that is, TI(=η 0.1 / η 10.0 ) may be 250 or less. From the viewpoint of uniform coating properties, the TI of the present composition is particularly preferably 100 or less, and more preferably in the range of 10 to 80.

[0125] [Solid content]

[0126] In the curable organopolysiloxane composition involved in the present invention, the content of the component that cures to form the organopolysiloxane cured product as a non-volatile solid component (sometimes simply referred to as "solid content" in the present invention) is preferably in the range of 5 to 100% by mass of the entire composition, and more preferably in the range of 50 to 100% by mass, 75 to 100% by mass, or 85 to 100% by mass.

[0127] [Introduction of dielectric functional groups]

[0128] When the organopolysiloxane cured product film involved in the present invention is used as an electroactive film (e.g., dielectric film) for transducers such as sensors and actuators, high dielectric functional groups can also be introduced into the cured product. However, even if the organopolysiloxane cured product film does not include high dielectric functional groups, it can also be used as an electroactive film. It should be noted that, about the introduction of these high dielectric functional groups and the improvement of relative dielectric constant, for example, it has been proposed in the international patent publication WO2014 / 105959 bulletin of the applicant of this case, etc.

[0129] The introduction of high dielectric functional groups can be carried out by using fluoroorganopolysiloxane or organohydrogenpolysiloxane having high dielectric functional groups as part or all of the above-mentioned component (a) or component (b), or by adding an organic additive having high dielectric functional groups, a non-reactive organosilicon compound having high dielectric functional groups, etc. to the above-mentioned curable composition.

[0130] The type of high dielectric functional group introduced into the organopolysiloxane cured film is not particularly limited, and examples thereof include: a) halogen atoms and groups containing halogen atoms represented by 3,3,3-trifluoropropyl, etc., b) groups containing nitrogen atoms represented by cyanopropyl, etc., c) groups containing oxygen atoms represented by carbonyl, etc., d) heterocyclic groups such as imidazole, e) groups containing boron such as borate, f) groups containing phosphorus such as phosphine, and g) groups containing sulfur such as thiol. Preferably, halogen atoms containing fluorine atoms and groups containing halogen atoms are preferably used.

[0131] The curable organopolysiloxane composition of the present invention can be prepared by uniformly mixing the curable organopolysiloxane with a component that accelerates the curing reaction, preferably the above-mentioned components (a) to (e), and can also be prepared by adding other arbitrary components as needed and uniformly mixing. Mixing can be performed at room temperature using various stirrers or kneaders, but if the combination is a combination of components that do not cure during mixing, mixing can also be performed under heating.

[0132] If the mixture is not cured during mixing, the order of mixing the components is not particularly limited. After mixing, when not used immediately, the crosslinking agent (e.g., component (b)) and the component that accelerates the curing reaction (e.g., component (c)) may be stored in multiple containers so that they are not in the same container, and the components in all containers may be mixed before use.

[0133] The curing reaction of the curable organopolysiloxane composition of the present invention is usually achieved by heating the composition or exposing it to active energy rays. The curing reaction temperature based on heat is not particularly limited, but is preferably 50°C to 200°C, more preferably 60°C to 200°C, and even more preferably 80°C to 180°C. Furthermore, the curing reaction can be carried out in one stage or in two or more stages, and after initial curing or semi-curing at a low temperature, full curing is carried out at a higher temperature, etc., which can be appropriately selected according to the manufacturing process of the laminate or transducer as the target.

[0134] In addition, the time taken for the curing reaction depends on the structure of the above-mentioned components (a), (b), (c) and (e) and the above-mentioned curing process, but is usually more than 1 second and less than 3 hours. Generally speaking, a cured product or a semi-cured product can be obtained by maintaining it in the range of 90 to 180° C. for 10 seconds to 120 minutes. It should be noted that the method for manufacturing the film will be described later.

[0135] As active energy rays that can be used for the curing reaction, ultraviolet rays, electron beams, and radiation can be listed, but ultraviolet rays are preferred in terms of practicality. In the case of using ultraviolet rays for the curing reaction, it is ideal to add a catalyst for the hydrosilylation reaction that has high activity relative to the ultraviolet rays used, such as bis(2,4-pentanedionate) platinum complex and (methylcyclopentadienyl) trimethyl platinum complex. As the ultraviolet light generating source, high-pressure mercury lamps, medium-pressure mercury lamps, Xe-Hg lamps, and deep ultraviolet lamps (Deep UV Lamp) are preferred, and the irradiation amount at this time is preferably 100 to 8,000 mJ / cm 2 In order to shorten the curing time or to continue the curing reaction at room temperature, irradiation with active energy rays and a thermal curing reaction may be used in combination.

[0136] [Cured organopolysiloxane]

[0137] The organopolysiloxane cured product obtained by curing the present composition preferably has a storage modulus (G') at 23°C which is within the range of 5.00 × 10 3 ~1.00×10 5 Pa, and at these measuring frequencies, its loss tangent is less than 0.3. More preferably, the organopolysiloxane cured product obtained by curing the present composition preferably has a storage modulus (G') at 23°C that is within the range of 1.00×10 4 ~7.50×10 4Pa, and at a measuring frequency of 1 Hz, its loss tangent is 0.05 to 0.29. It should be noted that, generally, the loss tangent of the above-mentioned organopolysiloxane cured product measured at a measuring frequency of 1 Hz is greater than the measured value at 0.1 Hz. The composition involved in the present invention provides viscoelastic properties (especially the above-mentioned storage modulus and loss tangent) to the organopolysiloxane cured product within the above-mentioned range through curing, so that good return characteristics after modification can be achieved, and it can be particularly suitable for use as a dielectric layer for a transducer.

[0138] The organopolysiloxane cured product of the present invention is preferably in the form of a film or sheet. In particular, the cured film obtained by curing the composition of the present invention can be preferably used as a dielectric layer in a transducer, and is particularly preferably in the form of an organopolysiloxane cured film for a transducer (hereinafter sometimes referred to as a "cured film for a transducer").

[0139] [Laminate as transducer and method for producing the same]

[0140] The organopolysiloxane cured product of the present invention can preferably be used as a dielectric layer for a transducer. The transducer film cured product as a dielectric layer may have an electrode layer on both sides (upper and lower layers), or may have a structure in which both sides (upper and lower layers) are sandwiched by substrate layers, or may have an electrode layer on one side and a substrate layer on the other side. Furthermore, the substrate layer may be an intermediate layer.

[0141] More specifically, the transducer of the present invention preferably has a structure in which at least one layer of the above-mentioned organopolysiloxane cured product is sandwiched between at least one pair of electrode layers. As a laminate of such a transducer, the dielectric layer composed of the organopolysiloxane cured product may have electrode layers on both sides (upper and lower layers), or may have a substrate layer or an intermediate layer between two or more dielectric layers and electrode layers on both sides (upper and lower layers), or may have two or more of these laminated structures.

[0142] At the interface between the transducer film cured product of the present invention and one or more layers selected from the electrode layer and the substrate layer, it is preferred that the film is at least partially bonded by chemical bonds, and when it is desired to peel the laminate, it is preferred that cohesive failure (CF) of the transducer film cured product is caused at the interface. In addition to the above-mentioned viscoelastic properties, the composition of the present invention also exhibits good adhesion to a variety of substrates.

[0143] The other layers constituting the laminated body involved in the present invention may be a synthetic resin layer such as a thermoplastic resin, a metal layer, or a silicone cured material layer containing conductive particles (an electrode layer, which is a layer different from the transducer film cured material of the present invention), and there is no particular limitation. However, when at least a portion of the electrode layer and / or the substrate layer is a thermoplastic resin layer (when it is an electrode layer, it is a thermoplastic resin layer containing conductive particles), by applying the curable organopolysiloxane composition for transducers involved in the present invention to at least a portion of these layers and curing them, a laminated body having a structure in which the two layers are bonded by at least partially forming a chemical bond at the interface of the two layers can be obtained. In particular, if the thermoplastic resin layer such as PET is a conventional silicone cured layer, sufficient adhesion / adhesion cannot be achieved, and the problem of interlayer peeling may sometimes occur when used as a transducer component. However, in the transducer film cured material of the present invention, the two can be firmly bonded and a high degree of followability can be achieved, which has the advantage of significantly improving the performance, reliability and durability as a transducer component.

[0144] The thermoplastic resin layer that can be used in the laminated body involved in the present invention is not particularly limited, but the thermoplastic resin film layer composed of polyethylene terephthalate (PET), polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polycarbonate, cyclic polyolefin, nylon, etc. can be exemplified. In particular, when heat resistance is required, films of heat-resistant synthetic resins such as polyimide, polyetheretherketone, polyethylene naphthalate (PEN), liquid crystal polyarylate, polyamide-imide, and polyethersulfone are preferred. On the other hand, in the use of display devices and the like requiring visual confirmation, transparent substrates can be used, specifically, transparent materials such as polypropylene, polystyrene, polyvinylidene chloride, polycarbonate, polyethylene terephthalate, and PEN. It should be noted that PET film is commonly used in industry, and the transducer film cured product of the present invention can be easily bonded to the PET film.

[0145] The substrate layer is preferably in the form of a film or a sheet. The thickness thereof is not particularly limited and can be designed to a desired thickness according to the application. Furthermore, in order to improve the adhesion between the substrate layer and the transducer film cured product, a primer treatment, a corona treatment, an etching treatment, or a plasma treatment may be used on the surface of the substrate layer in advance. However, in the present invention, since a chemical bond can be easily formed between the two, it has the advantage that an adhesive laminate can be easily obtained even without these pretreatments.

[0146] The method for obtaining such a laminate is not particularly limited, but it can be easily produced by a production method comprising the steps of applying the curable organopolysiloxane composition for transducers according to the present invention on at least one surface of one or more layers selected from an electrode layer and a substrate layer and curing the composition.

[0147] As a method for applying the curable organopolysiloxane composition to a film, gravure coating, offset coating, offset gravure, roll coating using an offset transfer roll coater, reverse roll coating, air knife coating, curtain coating using a curtain flow coater, comma blade coating, Mayer bar, and other well-known methods used for the purpose of forming a cured layer can be used without limitation. Furthermore, the curable organopolysiloxane composition of the present invention can also be applied in multiple layers.

[0148] The laminated body as a transducer of the present invention preferably has a chemically bonded structure at its interface of the laminated organopolysiloxane cured film, which is formed by contacting the organopolysiloxane cured film or a thin layer of a curable organopolysiloxane composition in an uncured or semi-cured state (state before complete curing) as its precursor after or before curing, and completely curing by heating or the like, thereby reacting between curable reactive groups at the interface of the cured film. From the viewpoint of industrial production and production efficiency, the process can be stacked by allowing the curing reaction to proceed in each layer, or by pre-stacked thin layers of a plurality of curable reactive curable organopolysiloxane compositions and then completely curing the whole by heating or the like.

[0149] More specifically, the laminated body involved in the present invention can be obtained by the following method: applying a curable organopolysiloxane composition for a transducer on at least one side of a layer selected from an electrode layer and a substrate layer, and then further stacking one or more other layers selected from the electrode layer and the substrate layer on the coating layer of the composition in an uncured or semi-cured state, and completely curing the whole. In addition, a laminated body precursor (for example, having a structure such as electrode layer / substrate layer / (uncured composition layer) / substrate layer / electrode layer, but not limited thereto) can also be prepared by stacking two or three or more layers selected from the electrode layer and the substrate layer, and having a coating layer composed of an uncured curable organopolysiloxane composition for a transducer between these layers, and curing the whole to prepare a laminated body having a cured film for a transducer between the layers.

[0150] This manufacturing method is particularly useful as a method for forming an electrode layer in a transducer component, and can easily provide a laminated body, electronic component or display device component in which the layers including the dielectric layer and the electrode layer are firmly bonded and are not prone to peeling or defects caused by insufficient bonding strength and followability.

[0151] The laminate of the organopolysiloxane cured film of the present invention is useful as an electronic material, a component for a display device, or a component for a transducer (including sensors, speakers, actuators, and generators), and can be used as an electroactive film (including a high dielectric film) with an electrode layer, preferably as a component of an electronic part or a display device. Further, as described above, the electroactive film with high dielectric breakdown strength is preferably a transducer component for an actuator, etc. in the form of a single layer or a laminated film, and in addition to good returnability after deformation, it also has a structure of strong bonding between layers, so it is particularly useful in sensors that require press-in operation or speakers with high deformation frequency, actuators that start at high voltage, and generators.

[0152] Industrial Applicability

[0153] The curable organopolysiloxane composition for transducer and its organopolysiloxane cured product involved in the present invention are gels or elastomers with excellent returnability after deformation, excellent electrical properties and mechanical properties, and can be designed to have high relative dielectric constant and mechanical strength (specifically, tensile strength, tear strength, elongation, etc.). Therefore, the electroactive organopolysiloxane elastomer sheet or electroactive organopolysiloxane gel sheet obtained by curing the above-mentioned organopolysiloxane composition into a film can be preferably used to constitute the electroactive film (dielectric layer or electrode layer) of the transducer. For example, it is useful as the transducer material proposed by the applicant and others in the above-mentioned patent document 1 or patent document 2. In addition, it can also be applied without special restrictions to transducer devices using dielectric elastomers other than silicone, and can be designed by replacing part or all of the dielectric elastomer layer with the above-mentioned cured product. Many structures of such transducers (including actuators) have been proposed, for example, WO2011 / 118315 as an international patent publication, Japanese Patent Publication No. 2008-533973, Japanese Patent Publication No. 2001-524278, Japanese Patent Publication No. 2008-187079, Japanese Patent Publication No. 2008-277729, Japanese Patent Publication No. 2009-59856, Japanese Patent Publication No. 2009-219302, Japanese Patent Publication No. 2012-65427, Japanese Patent Publication No. 2016-226258, Japanese Patent Publication No. 2017-064836, etc. It should be noted that the structural design or design change accompanied by the replacement of part or all of the dielectric elastomer layer using the above-mentioned cured product can be dealt with by the usual creation of those skilled in the art, and the present invention has a strong inspiration for such creation.

[0154] Similarly, the solidified material can also be used in place of the electrolyte layer or dielectric layer in the actuator element structure known as the so-called "polymer actuator" or "polymer actuator". Specifically, it can be used in place of a part or all of the electrolyte layer in a polymer actuator having an electrolyte layer (including an electrolyte layer containing an ionic liquid in a polymer) and an electrode layer formed on the electrolyte layer, and deformed according to the voltage applied to the electrolyte layer. It should be noted that many structures of such polymer actuators have been proposed, including: WO10 / 100907, WO10 / 110417, WO11 / 114965, WO10 / 029992, WO13 / 118628, WO14 / 104331 as international patent publications; Japanese Patent Publication No. 2004-282992, ... No. 2008-251697, Japanese Patent No. 2010-003553, Japanese Patent No. 2012-055153, Japanese Patent No. 2013-255397, Japanese Patent No. 2013-106491, Japanese Patent No. 2013-251942, Japanese Patent No. 2015-126597, Japanese Patent No. 2015-186301, Japanese Patent No. 2016-189651, etc. It should be noted that the organopolysiloxane cured product involved in the present invention is different from electrolyte, can be designed as desired shape with elastomer or gel, particularly, it is useful to seek the structural design of stacking or high displacement. Therefore, in existing polymer actuator, structural design or design change reflecting above-mentioned mechanical properties and dielectric properties can be dealt with by the common creation of those skilled in the art, and the present invention has strong enlightenment to such creation.

[0155] Example

[0156] The present invention will be described below with reference to Examples, but the present invention is not limited to these Examples. The following compounds were used in the Examples shown below.

[0157] Component (a1): dimethylsiloxane polymer (vinyl content: 0.22 mass %, weight average molecular weight (Mw): 3.99×10 4 ).

[0158] Component (a2): dimethylsiloxane polymer (vinyl content: 0.14 mass %, Mw: 5.97 × 10 4 ).

[0159] Component (a3x): dimethylsiloxane polymer (vinyl content: 0.09 mass %, Mw: 9.95×10 4 ).

[0160] In addition, Mw of a component (a) is the weight average molecular weight measured by GPC (gel permeation chromatography) using toluene as a solvent and converted into polystyrene.

[0161] Component (b1): a dimethylsiloxy-methylhydrosiloxy-siloxane copolymer terminated at both ends by trimethylsiloxy groups (silicon-bonded water content: 0.70 mass %)

[0162] Component (b2): dimethylsiloxane polymer terminated at both ends by dimethylhydrogensiloxy groups (silicon-bonded water content: 0.02 mass %)

[0163] Component (c): a dimethylsiloxane polymer solution capped with vinyldimethylsiloxy groups at both ends of a platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex (about 0.6% by weight based on platinum concentration)

[0164] Component (d): fumed silica treated with hexamethyldisilazane (product name before treatment: AEROSIL200)

[0165] Component (e): Adhesion improver (=reaction product of methylvinylsiloxane and glycidoxypropyltrimethoxysilane capped with hydroxydimethylsiloxy groups at both ends (the vinyl content (weight %) is within the range of about 5.2 to 5.6))

[0166] <Hydrosilylation Reaction Inhibitor>

[0167] Component (f): 1-ethynyl-1-cyclohexanol

[0168] [Examples 1 to 10, Comparative Examples 1 to 3]

[0169] The composition of each experimental example is shown in Table 1 (Example) and Table 2 (Comparative Example). The numerical value corresponding to each component is mass %, and the sum is 100 mass %. In addition, in the following examples, the silicon atom-bonded hydrogen atom (Si-H) of the component (d) as the crosslinking agent is used in an amount ranging from 0.54 to 0.76 moles per 1 mole of the vinyl group (unsaturated hydrocarbon group, the same below) in the composition. At this time, the p in the composition is xl Value and MW(a) / p xlThe values ​​were set as described in Tables 1 and 2. When mixing the components, the materials were finally mixed in a rotation / revolution mixer (product name ARV-310LED, manufactured by THINKY Corporation) under vacuum for preparation.

[0170] [Viscosity of composition before curing]

[0171] The viscosity of each composition before curing was measured using a viscoelasticity measuring device (manufactured by Anton Paar, model MCR302). A cone plate with a diameter of 20 mm and a shear rate of 2° was used to measure the viscosity. The viscosity of each composition before curing was recorded at 25°C and a shear rate of 0.1 (S -1 ) and 10.0(S -1 ) The overall viscosity of the composition was measured. The viscosity values ​​are shown in Tables 1 and 2, respectively.

[0172] [Preparation of cured product sheets]

[0173] Each composition was sandwiched between Teflon (registered trademark) films having a thickness of about 150 μm, press-cured at 70° C. for 60 minutes, and post-cured in an oven at 130° C. for 60 minutes to obtain a cured sheet having a thickness of about 2 mm.

[0174] [Storage modulus and loss modulus]

[0175] The viscoelasticity of each cured sheet obtained as described above was measured using a viscoelasticity measuring device (manufactured by Anton-paar, model MCR302). A Peltier element temperature control system and a parallel plate with a diameter of 8 mm were used to set the sample in a manner to have a thickness of about 2 mm. The measurement was performed by frequency scanning at 23°C under a slight deformation (about 0.2%). The storage modulus (G'), loss modulus (G") and loss tangent at 0.1 and 1.0 Hz are shown in Tables 1 and 2.

[0176] [Adhesion Evaluation]

[0177] About 1 g of the curable organopolysiloxane composition was applied to a 200 μm thick polyethylene terephthalate film and cured at 130° C. for 1 hour. The cured product was then peeled off using a scraper, and the peeling mode was visually evaluated based on the presence or absence of cured product residues to determine whether it was interfacial peeling (AF) or cohesive failure (CF). The results are shown in Tables 1 and 2.

[0178] [Table 1]

[0179]

[0180]

[0181] [Table 2]

[0182]

[0183]

[0184] [Summarize]

[0185] As described above, in Examples 1 to 10, the weight average molecular weight (Mw(a)) of component (a) and the x1 The value obtained by dividing the Mw(a) of each component by the value of is set within the optimal range, and the G' of the composition after curing is set to 1.0×10 4 ~1.0×10 5 Pa, while being able to maintain the loss tangent below 0.3. Furthermore, it was confirmed that the organopolysiloxane cured product of the present invention has significantly excellent mechanical properties, and therefore is preferably used in various transducer applications such as sensors and actuators, in which the return characteristics after deformation caused by external stress are preferred.

[0186] On the other hand, as in Comparative Examples 1 to 3, if the weight average molecular weight and the ratio of p are not set at a predetermined ratio, x1 If the value obtained by dividing Mw(a) by the value of , the viscoelasticity described above cannot be obtained, and the electroactive film or electroactive sheet cannot be fully utilized as an electroactive film or electroactive sheet for various transducer applications represented by actuators.

[0187] The cured product obtained by using the curable organopolysiloxane composition according to the embodiment of the present invention can be designed to have excellent adhesion to a substrate and to have both flexibility and responsiveness, and can be widely used.

Claims

1. A curable organopolysiloxane composition for a transducer, comprising: The weight average molecular weight (Mw(a)) of the component (a) is less than 8.0×10 4 , a linear or branched organopolysiloxane or a mixture thereof having at least two curing reactive groups containing a carbon-carbon double bond in the molecule; (b1) an organohydrogenpolysiloxane having at least one silicon-bonded hydrogen atom in a side chain portion of the molecular chain, having no silicon-bonded hydrogen atom at at least one end of the molecular chain, and having at least two silicon-bonded hydrogen atoms in the molecule; (b2) an organohydrogenpolysiloxane having silicon-bonded hydrogen atoms at both ends of the molecular chain and at least two silicon-bonded hydrogen atoms in the molecule; and (C) an effective amount of a catalyst for a hydrosilylation reaction, About this composition The amount of silicon-bonded hydrogen atoms in component (b1) (H b1 ), The amount of hydrogen atoms bonded to silicon atoms in component (b2) (H b2 ),as well as The amount of curing reactive groups containing carbon-carbon double bonds in component (a) (Vi), By the following relationship: p x1 ={H b1 / H b2 } / {(H b1 +H b2 ) / Vi} Defined p xl The value obtained by dividing Mw(a) by the value of is in the range of 1,000 to 8,000.

2. The curable organopolysiloxane composition for transducer according to claim 1, wherein The total amount of silicon-bonded hydrogen atoms in components (b1) and (b2) is in the range of 0.1 to 0.99 mol per 1 mol of carbon-carbon double bonds in component (a).

3. The curable organopolysiloxane composition for transducer according to claim 1, wherein Component (a) is a linear or branched organopolysiloxane having a curing reactive group containing a carbon-carbon double bond at both ends of the molecular chain, or a mixture thereof.

4. The curable organopolysiloxane composition for transducer according to claim 1, characterized in that: Further comprising (d) a reinforcing filler.

5. The curable organopolysiloxane composition for transducer according to claim 1, characterized in that: The invention further comprises (e) a tackifier.

6. The curable organopolysiloxane composition for transducer according to claim 1, wherein The viscoelasticity was measured at 25°C using a viscoelasticity measuring apparatus at a shear rate of 0.1 (S -1 ) The overall viscosity of the composition measured is in the range of 100 to 2,000 Pa·s.

7. The curable organopolysiloxane composition for transducer according to claim 1, wherein: The storage modulus (G') of the organopolysiloxane cured product obtained by curing the composition at 23°C is 5.00×10 3 ~1.00×10 5 Pa, and at these measurement frequencies, its loss tangent is less than 0.

3. 8 . An organopolysiloxane cured product obtained by curing or semi-curing the curable organopolysiloxane composition for a transducer according to claim 1 .

9. The organopolysiloxane cured product according to claim 8, wherein The organopolysiloxane cured product is in the form of a film or a sheet.

10. The cured organopolysiloxane according to claim 8, wherein The organopolysiloxane cured product is used for at least one application selected from the group consisting of a transducer member, an electronic material, and a display device member.

11. The cured organopolysiloxane according to claim 8, wherein The organopolysiloxane cured product is a dielectric layer for a transducer. 12 . A transducer having a structure in which at least one layer of the cured organopolysiloxane according to claim 8 is sandwiched between at least a pair of electrode layers. 13 . A method for producing a transducer, comprising at least the steps of applying the curable organopolysiloxane composition for a transducer according to claim 1 in a film or sheet form and curing or semi-curing the composition.

Citation Information

Patent Citations

  • Elastic dielectric polymer film acoustic actuator

    JP2001524278A

  • Actuator element and drive method

    JP2004282992A

  • Dielectric elastomer film for electrostriction type actuator and its manufacturing method

    JP2008187079A

  • Polymer actuator

    JP2008251697A

  • Actuator

    JP2008277729A